Residual stress study of welded high strength steel thin-walled plate-to-plate joints, part 2 : numerical modeling - Chiew, Sing Ping (2014)
In the Part 2 of the current study, a sequentially coupled thermal-stress analysis is conducted to model the welding process and the final residual stress distribution of the RQT701 high strength steel thin-walled plate-to-plate welded joints. The accuracy and reliability of the numerical modeling is validated by comparing with the test results. After validating the accuracy of the modeling procedure, a small scale parametric study is carried out to investigate the influences of some key welding parameters on the magnitude and distribution of residual stress.